Insights into messy chemistry related to cosmology and origin of life obtained by employing state-of-the-art computational methods - Das, T. (CSIR-National Chemical Laboratory, 2021)
How life began on the early earth, as well as how small molecules and ions were first formed at the beginning of the universe are some of the biggest unsolved questions in science that have intrigued researchers over time. However, no clear answers have yet been received for researchers in the fields of cosmology, prebiotic chemistry, interstellar chemistry as well as astrochemistry. From previous studies, it has become clear that the creation of the universe and the origin of life are not the result of any single event. Rather, they are likely the product of highly complex or “messy” chemical processes. In this chapter, an overview has been provided on how messy chemistry plays a role in cosmology, as well as in prebiotic chemistry. In this thesis work, by employing state-of-the-art computational methods especially ab initio molecular dynamics (AIMD) with nanoreactor approach and quantum chemical calculations with RICC2, RIMP2 and DFT has been carried out to explore some unsolved questions in the area of cosmology and prebiotic chemistry. We have concentrated into this area of research not only because of the general interest and scientists have done hundreds of chemical experiments in this field but also explore or discover new chemistry through computational perspective because there are several questions that have not been completely explored. Hence, in this thesis, three critical areas of the Universe: a) cosmology, b) prebiotic chemistry, and c) interstellar space chemistry where messy chemistry could play an important role in the reaction network, have been demonstrated.
Keywords: Natural Sciences